Communication science: An integral part of business and business studies? - Michael B. Hinner (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2002)
Communication is at the center of any business transaction. Unfortunately until recently, communication has rarely been assigned its proper relevance in traditional business studies at German universities. This paper attempts to demonstrate why communication science can and should be an integral part of all business studies. Without understanding the pertinent communication principles, it will not be possible to fully understand specific business relationships. With understanding, more effective and efficient use of communication in business relationships will become possible. This paper, therefore, briefly outlines the role of communication in some areas of business and then proceeds to sketch a succinct communication model to illustrate how communication affects business relationships. The paper ends with a concrete example, namely that of the TU Bergakademie Freiberg, of how communication science may be integrated as a distinct subject into the curriculum of business studies. – – Kommunikation stand schon immer im Mittelpunkt jeder Wirtschafts- und Geschäftsbe-ziehung. Leider wurde der Kommunikation bis vor kurzem jedoch keine eigenständige Rolle in wirtschaftswissenschaftlichen Curricula an deutschen Universitäten zugesprochen. Dieses Arbeitspapier versucht darzulegen, warum Kommunikationswissenschaft ein integraler Teil aller wirtschaftswissenschaftlichen Curricula sein sollte. Denn ohne ein wahres Verständnis der relevanten Prinzipien der Kommunikation ist es nicht möglich, viele Wirtschafts- und Geschäftsbeziehungen tiefgreifend zu verstehen. Demzufolge beschreibt dieses Arbeitspapier in knappen Zügen die Bedeutung der Kommunikation für einige Bereiche der Wirtschaft, um dann im Rahmen einer kurzen Beschreibung des Kommunikationsmodells darzulegen, wie die Kommunikation diese Beziehungen beeinflusst. Anhand des Beispiels der Fakultät für Wirtschaftswissenschaften an der TU Bergakademie Freiberg wird abschließend erläutert, wie die Kommunikationswissenschaft in ein wirtschaftswissenschaftliches Curriculum integriert werden kann.
Keywords: A12; A2; M14; Z13; 330; Business Communication; Intercultural Communication; Communication Process; Business English Curriculum; Wirtschaftskommunikation; Interkulturelle Kommunikation; Kommunikationsprozess; Wirtschaftsenglisch Curriculum; Kommunikationswissenschaft; Wirtschaftswissenschaft; Wirtschaftsstudium